2008
DOI: 10.1143/jjap.47.1491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Implantation with Low Dose on Thermomechanical Properties and Microstructure of Ge2Sb2Te5 Films

Abstract: Ge 2 Sb 2 Te 5 (GST) films with a thickness of 300 nm, in which the nitrogen (N) implant dose was 0, 10 13 , or 10 15 ions/cm 2 , were prepared by RF magnetron sputtering on Si and glass substrates. The thermomechanical properties of the GST films, viz., the biaxial modulus and coefficient of thermal expansion (CTE), were determined using the substrate curvature method for the two different substrates. The biaxial modulus of the GST films decreased with increasing N dose, whereas the CTE varied only slightly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This suggested that the nitrogen atoms occupy either vacancies or tetrahedral interstitial sites, causing a shift in the characteristic peaks and increase of the lattice parameter. Direct phase transition to the hcp phase was also verified with nitrogen implantation [24,25]. A nitrogen implantation dose higher than 4.51 × 10 16 cm −2 resulted in direct transition from the amorphous phase to the hcp phase, with suppression of the fcc phase [24].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…This suggested that the nitrogen atoms occupy either vacancies or tetrahedral interstitial sites, causing a shift in the characteristic peaks and increase of the lattice parameter. Direct phase transition to the hcp phase was also verified with nitrogen implantation [24,25]. A nitrogen implantation dose higher than 4.51 × 10 16 cm −2 resulted in direct transition from the amorphous phase to the hcp phase, with suppression of the fcc phase [24].…”
Section: Introductionmentioning
confidence: 78%
“…Many researchers are also interested in suppressing the rocksalt phase or the hexagonal-close-packed (hcp) phase of GST by doping it with an appropriate element to make it a potential candidate in various applications. The suppression of these phases of GST was reported by various researchers using different doping materials [21][22][23][24][25][26][27]. Seo et al [21] found that addition of 10% Al to Ge 2 Sb 2 Te 5 served as a center for the suppression of fcc-to-hcp transition, which led to a single-step crystallization process (i.e., amorphous to fcc phase).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation